2013
DOI: 10.1002/star.201300058
|View full text |Cite
|
Sign up to set email alerts
|

Starch physicochemical properties of rice accessions and their association with molecular markers

Abstract: The grain quality of rice has recently attracted a lot of attention around the world, including Africa. Rice germplasm in African gene banks has not been adequately characterized for its cooking and eating qualities which are mainly controlled by starch physicochemical properties. The aim of this study was to characterize two groups of rice germplasm from Africa and the U.S. for starch properties including gelatinization temperature (GT), apparent amylose content (AAC), and paste viscosity (RVA), and to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 26 publications
3
24
1
Order By: Relevance
“…Among over twenty starch biosynthesis related genes, Waxy gene was reported as the primary gene responsible for amylose content by multiple QTL mapping studies (He et al, 1999; Tan et al, 1999; Septiningsih et al, 2003; Xu et al, 2015). In the previous association analyses, a total of five polymorphic sites in Waxy gene were reported as having important effects on AAC variation (Ayres et al, 1997; Larkin and Park, 2003; Wanchana et al, 2003; Chen et al, 2008; Asante et al, 2013; Caffagni et al, 2013). In our association analyses, we included five markers specific to all the five polymorphic sites (G/T SNP of intron 1, 23 bp InDel of exon 2, G/C SNP of exon 6 and C/T SNP of exon 10, and (CT) n repeats) in order to compare their relative importance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among over twenty starch biosynthesis related genes, Waxy gene was reported as the primary gene responsible for amylose content by multiple QTL mapping studies (He et al, 1999; Tan et al, 1999; Septiningsih et al, 2003; Xu et al, 2015). In the previous association analyses, a total of five polymorphic sites in Waxy gene were reported as having important effects on AAC variation (Ayres et al, 1997; Larkin and Park, 2003; Wanchana et al, 2003; Chen et al, 2008; Asante et al, 2013; Caffagni et al, 2013). In our association analyses, we included five markers specific to all the five polymorphic sites (G/T SNP of intron 1, 23 bp InDel of exon 2, G/C SNP of exon 6 and C/T SNP of exon 10, and (CT) n repeats) in order to compare their relative importance.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (2008) measured 53 rice accessions with this T SNP, and nearly all of them showed AAC <18%. However, several studies reported some rice cultivars with the TAC waxy haplotype had AAC > 18% (Dobo et al, 2010; Asante et al, 2013; Caffagni et al, 2013; Biselli et al, 2014). Our present result also showed that the T SNP in intron 1 of Waxy gene is not always accompanied by an AAC lower than 18% (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wide variation amongst AAC, pasting and thermal parameters is observed in cultivated rice germplasm (Asante et al, 2013 Tables 1 and 2 for the abbreviations. *, ** indicate significance at P < 0.05 and 0.01 levels, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately this could result in reduced retrogradation of amylose molecules [38]. High values in breakdown and low values in setback of semi-wet ground flour are indicative of high cooking quality since neither the cooked rice retrogrades nor becomes stiff upon cooling [39].…”
Section: Figure 2 Microscopic Structure Of Dry (A) Semi-wet (B) Andmentioning
confidence: 99%